Exploring the intricacies and dissonances of religious governance: The case of Quebec and the discourse of request - Barras, Amélie (Critical research on religion, 2016)
This article interrogates the extent to which institutional discourses on the governance of religious minorities are useful to think about the complexity of how religion gets negotiated in the quotidian. It takes as its starting point the exploration of the discourse on religious governance in the province of Quebec organized around the notion of request for accommodations. Through an analysis of public policy documents, it examines facets of this discourse of request, including the role it plays in delimiting what we imagine the religious (and Islam, in particular) to be and how we imagine it to work. Second, drawing on interviews with self-identified Muslims in Montreal, the article explores how piety gets negotiated in their everyday. These narratives are approached as fertile sites to think differently about the recognition of difference. This two-pronged perspective acts as an invitation to think more broadly about not only what institutional discourses "produce" but also what they "obscure."